연령관련황반변성환자에서 항혈관내피성장인자의 국내 사용 현황 - 조송희(Songhee Cho), 신상진(Sang Jin Shin), 서재경(Jae Kyung Suh), 최하진(Hajin Tchoe), 강민주(Min Joo Kang), 양장미(Jangmi Yang), 지동현(Donghyun Jee) (Daihan angwa haghoi jabji, 2019)
목적: 연령관련황반변성환자에서 항혈관내피성장인자의 유리체내주입술의 국내 사용 현황을 알아보고자 하였다. 대상과 방법: 국민건강보험공단의 청구 자료(2007-2016년)를 이용하여 연령관련황반변성으로 진단받은 환자들을 대상으로 항혈관내피성장인자를 주입받은 환자들의 규모와 의료비를 분석하였다. 연령관련황반변성환자들의 항혈관내피성장인자 주입술의 사용 횟수, 사용 주기, 평균 의료 비용 등을 분석하였다. 또한 신환자의 규모와 항혈관내피성장인자 주입술의 사용 현황을 조사하였다. 결과: 연령관련황반변성 유병환자 수는 2009년 236,158명이었으나 2016년 기준 537,528명으로 7년 사이 2.3배 증가하였다. 이 중에서 항혈관내피성장인자 주입술을 시행받은 환자들의 규모는 2009년 9,961명에서 2016년 35,762명으로 증가하였다. 라니비주맙 또는애플리버셉트의 1인당 평균 사용 횟수는 약 4.87 ± 3.37회로 나타났으며 평균 치료 간격은 2.89개월로 확인되었다. 진단받은 첫 해에 평균 6.2회의 주입술을 받았고, 시간이 흐를수록 사용 횟수가 줄어들어 진단 4년이 지난 뒤에는 평균 1.2회의 사용 횟수를 보였다. 항혈관내피성장인자 치료를 받은 환자의 전체 의료비는 769억 원이었으며, 1인당 평균 의료 비용은 2,162,145원이었다(2016년 기준). 결론: 국민건강보험공단 건강보험 청구자료를 이용하여 급여 약제인 라니비주맙, 애플리버셉트의 사용 현황을 살펴본 결과 두 약제의 사용량은 꾸준히 증가하고 있었다. Purpose: To evaluate the current use of intravitreal injections of anti-vascular endothelial growth factor (anti-VEGF) in patients with age-related macular degeneration (AMD). Methods: We analyzed the number and medical costs of patients with AMD diagnosed by the National Health Insurance Corporation (2007–2016). We also analyzed the number and medical costs of such patients who received anti-VEGF treatment, and analyzed the frequency, period of use, and average medical cost of anti-VEGF use in AMD patients. Finally, we evaluated the use of anti-VEGF injections for new AMD patients. Results: The number of patients with AMD was 236,158 in 2009 and 537,528 in 2016, which represented a 2.3-fold increase over 8 years. Of these, the number of patients undergoing anti-VEGF therapy increased steadily from 9,961 in 2009 to 35,762 in 2016. The mean number of cycles of ranibizumab or aflibercept per patient was 4.87 ± 3.37, and the mean interval between treatments was 2.89 months. On average, 6.2 injections were performed in the first year of diagnosis, and the frequency of use decreased with time, with an average of 1.2 cycles after 4 years of diagnosis. Among all AMD patients in 2016, the total medical cost of those treated with anti-VEGF was 76.9 billion won, and the average medical cost per person was 2,162,145 won. Conclusions: The use of two drugs, ranibizumab and aflibercept, as reflected in public health insurance claims, steadily increased over the study period. Notably, there was a tendency to substitute aflibercept for ranibizumab. KCI Citation Count: 0